Identification of beneficial Lebanese Trichoderma spp. wheat endophytes - Matar, Naeif; Macadré, Catherine; Ammar, Gamal A. G.; Peres, Alexis; Collet, Boris; Boustany, Naim El; Rajjou, Loïc; As-Sadi, Falah; Dufresne, Marie; Ratet, Pascal (Frontiers in Plant Science, 2022)
Wheat is one of the most important crops in the world. Its production can be influenced by a diversity of beneficial and pathogenic rhizospheric microbes, including fungi. Amongst them, beneficial Trichoderma spp. can be used as alternatives to chemical fertilizers, as they are cheaper and harmless to the environment. Our study aimed to isolate, identify, and characterize Trichoderma spp. from Lebanon associated with wheat. Two Trichoderma strains belonging to T. afroharzianum, and T. guizhouense species, were isolated and found to be endophytes, enhancing root growth and producing IAA. Inoculation also improved seedling development, and boosted general production. Furthermore, the two strains inhibit Fusarium growth in vitro. These Trichoderma spp. have thus the capacity to be used as organic fertilizers for wheat.